2020
DOI: 10.1177/0047281620966990
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining Business Planning, Accessibility, and Web Design Instruction: A Stacked Interdisciplinary Collaboration Across National Boundaries

Abstract: The authors present the results of a study of a three-way international collaboration project among one Hungarian class and two classes from Michigan and Washington, respectively. This multifaceted study focused on business planning, web design, and accessibility with the aim of investigating the effect of accessibility instruction on the production of business plans and websites. The distinguishing feature of this study was its emphasis to orient the three student groups on disability and accessibility issues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Consequently, our research approval at this time allows somewhat limited use of student work in our publications. (For more details about the purpose and nature of this international, intercultural collaboration, see Koris et al, 2019;Oswal & Palmer, 2018;Palmer et al, 2020). We, nevertheless, chose this example of participatory action research pedagogy because it was successful in achieving the desired results, required limited planning on behalf of the group, and affected the whole class' overall understanding about disabled user experience, accessibility issues, and the value of participatory design research itself.…”
Section: An Example Of Participatory Action Research In the Classroommentioning
confidence: 99%
“…Consequently, our research approval at this time allows somewhat limited use of student work in our publications. (For more details about the purpose and nature of this international, intercultural collaboration, see Koris et al, 2019;Oswal & Palmer, 2018;Palmer et al, 2020). We, nevertheless, chose this example of participatory action research pedagogy because it was successful in achieving the desired results, required limited planning on behalf of the group, and affected the whole class' overall understanding about disabled user experience, accessibility issues, and the value of participatory design research itself.…”
Section: An Example Of Participatory Action Research In the Classroommentioning
confidence: 99%
“…The same 15 questions were repeated on the post-project survey in past tense and with additional questions that related to students' experiences with the project. The data analysis presented here focuses only on a subset of these 15 questions that are directly related to our main research questions (for a detailed list of all research questions, see Appendix A in Palmer et al, 2020). The additional questions probed students' perceptions about the effectiveness of this project with teaching business communication, intercultural communication, and accessibility know-how.…”
Section: Description Of the Quantitative Data And Analysismentioning
confidence: 99%
“…As educators from three different disciplines, at different universities, teaching graduate and undergraduate students from two countries, we have designed and taught an ambitious interdisciplinary virtual exchange that has now completed its second iteration. Through this experience and the data collected from it, we have found that such collaborations can answer the call for projects that promote both interdisciplinary experience and student learning around issues of disability awareness and accessibility (see Palmer et al, 2020 for discussion of the results of the first year of this virtual exchange.) As disability laws across the European Union (Waddington & Lawson, 2010) and in the United States (Americans with Disabilities Act, 1990) ascribe equal rights to disabled persons, accessibility know-how is not only a civic duty but is also a practical business skill.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations